The The stigma effect in the Land of Fires: the impact of negative environmental externalities on residential property values - Pierfrancesco De Paola; Orazio Campo; Valeria Scarica; Maria Laudando; Valentina Liguoro; Mario Ferraro (Aestimum)
The “Land of Fires” is an area extending between the provinces of Naples and Caserta (Italy). This vast region is notoriously affected by the burial and illegal disposal of toxic and special waste in abandoned quarries or unauthorized landfills, with waste often being burned, triggering numerous toxic fires. These phenomena create a “stigma effect” on the livability of the area under examination, with the local population suffering the most significant consequences. Residents are forced to live in a territory where mortality and cancer incidence rates are significantly higher than the national average. The primary objective of this study is to assess how environmental and social quality in the “Land of Fires” influence prices in the local real estate market. The first part of the study delves into the issues of urban quality in this context and its impact on residential property prices. The second part focuses on a specific portion of the “Land of Fires”, known as the “Triangle of Death” which includes the municipalities of Acerra, Marigliano, and Nola, with the aim of evaluating the geospatial variability of real estate values.